The gut microbe Bacteroides fragilis ameliorates renal fibrosis in mice - Zhou, Wei; Wu, Wen-hui; Si, Zi-lin; Liu, Hui-ling; Wang, Hanyu; Jiang, Hong; Liu, Ya-fang; Alolga, Raphael N.; Chen, Cheng; Liu, Shi-jia; Bian, Xue-yan; Shan, Jin-jun; et al. (Nature communications, 2022)
Renal fibrosis is an inevitable outcome of various manifestations of progressive chronic kidney diseases (CKD). The need for efficacious treatment regimen against renal fibrosis can therefore not be overemphasized. Here we show a novel protective role of Bacteroides fragilis ( B. fragilis ) in renal fibrosis in mice. We demonstrate decreased abundance of B. fragilis in the feces of CKD patients and unilateral ureteral obstruction (UUO) mice. Oral administration of live B. fragilis attenuates renal fibrosis in UUO and adenine mice models. Increased lipopolysaccharide (LPS) levels are decreased after B. fragilis administration. Results of metabolomics and proteomics studies show decreased level of 1,5-anhydroglucitol (1,5-AG), a substrate of SGLT2, which increases after B. fragilis administration via enhancement of renal SGLT2 expression. 1,5-AG is an agonist of TGR5 that attenuates renal fibrosis by inhibiting oxidative stress and inflammation. Madecassoside, a natural product found via in vitro screening promotes B. fragilis growth and remarkably ameliorates renal fibrosis. Our findings reveal the ameliorative role of B. fragilis in renal fibrosis via decreasing LPS and increasing 1,5-AG levels. Renal fibrosis is the main pathological feature of chronic kidney disease (CKD). Here, the authors show that live B. fragilis can attenuate renal fibrosis via the upregulation of SGLT2, which contributes to renal reabsorption of 1,5-AG, and that 1,5-AG improves renal fibrosis via inhibition of oxidative stress and inflammation.